Oxidative balance score is independently associated with reduced prevalence of sarcopenia among US adults with metabolic syndrome - Wang, Miaohong; Shi, Huan (Frontiers in Nutrition, 2025)
BackgroundThis research seeks to explore the link between the oxidative balance score (OBS) and sarcopenia in American adults with Metabolic Syndrome (MetS) using data from a national, population-based survey.MethodsThe study included 3,625 participants diagnosed with Metabolic Syndrome, all aged 20 years and above, derived from NHANES datasets spanning 1999–2006 and 2011–2018. OBS evaluation was based on 16 dietary and 4 lifestyle elements. MetS diagnosis followed the NCEP-ATP III guidelines, while sarcopenia identification was based on FNIH standards. We employed multivariate logistic regression analyses to delve into the connections between OBS and sarcopenia within the MetS cohort.ResultsSarcopenia was found in 17.46% of the participants. In models adjusted for all variables, OBS, dietary OBS, and lifestyle OBS each showed a significant inverse relationship with sarcopenia among MetS individuals [OBS: OR = 0.959, 95%CI: (0.948, 0.982), P trend = 0.0005; dietary OBS: OR = 0.963, 95%CI: (0.939, 0.989), P trend = 0.0055; lifestyle OBS: OR = 0.860, 95%CI: (0.787, 0.939), P trend = 0.0011]. Higher scores in OBS were consistently linked with a decreased incidence of sarcopenia (all P for trend < 0.05). Restricted cubic spline analysis confirmed that these relationships were linear. The impact of age was significant, with OBS benefits only observed in those aged 40 and older.ConclusionsMaintaining a diet and lifestyle rich in antioxidants is both independently and collectively linked with a lower occurrence of sarcopenia in individuals with MetS. These results bolster the proposition of developing OBS-centered preventive strategies for sarcopenia in MetS patients, particularly those aged 40 years and older.